The manager as facilitator of dialogue - Joseph A. Raelin (Organization, 2012)
In this article a new role for managers is advocated to create conditions for genuine collaborative engagement in 21st Century organizations. The new role is as a facilitator of emancipatory dialogue, a discourse among parties that can lead to mutual learning, deep understanding and insight, and collaborative consciousness and action. The facilitator role is described and illustrated in the article as a means to encourage free expression and inquiry, but the article also warns about the imposition of coercive norms within the work group that might be externally imposed or even self-imposed. As managers promote an emancipatory form of dialogic engagement, conversations ensue that bring out people's individual and collective wisdom, creativity, and dignity.
Keywords: D23; J52; M10; M14; M53; M54; 330; Facilitation; Dialogue; Deliberation; Emancipation; Managerial role; Post-bureaucracy; Critical management studies; Bohmian dialogue